PERIOCULAR CORTICOSTEROID INJECTIONS IN UVEITIS: EFFECTS AND COMPLICATIONS - Sen, H. Nida (Ophthalmology, 2014)
PURPOSE: To evaluate the benefits and complications of periocular depot corticosteroid injections in patients with ocular inflammatory disorders. DESIGN: Multicenter retrospective cohort study. PARTICIPANTS: A total of 914 patients (1192 eyes) who had received at least one periocular corticosteroid injection at 5 tertiary uveitis clinics in the United States. METHODS: Patients were identified from the Systemic Immunosuppressive Therapy for Eye Diseases (SITE) Cohort Study. Demographic and clinical characteristics were obtained at every visit via medical record review by trained reviewers. MAIN OUTCOME MEASURES: Control of inflammation, improvement of visual acuity to 20/40 or better, improvement of visual acuity loss attributed to macular edema, incident cataract affecting visual acuity, cataract surgery, ocular hypertension and glaucoma surgery. RESULTS: Among 914 patients (1192 eyes) who received at least one periocular injection during follow-up, 286 (31.3%) were classified as having anterior uveitis, 303 (33.3%) as intermediate uveitis, 324 (35.4%) as posterior or panuveitis. Cumulatively by ≤6 months, 72.7% [95% confidence interval (95%CI): 69.1-76.3] of the eyes achieved complete control of inflammation and 49.7% [95%CI:45.5-54.1] showed an improvement in visual acuity (VA) from worse than 20/40 to 20/40 or better. Among the subset with VA worse than 20/40 attributed to macular edema, 33.1% [95%CI: 25.2-42.7] improved to 20/40 or better. By 12 months, the cumulative incidence of one or more visits with an intraocular pressure≥24 mmHg and ≥30 mmHg was 34.0% [95%CI: 24.8-45.4] and 15.0% [95%CI: 11.8-19.1] respectively; glaucoma surgery was performed in 2.4% [95%CI: 1.4-3.9] of eyes. Within 12 months, among phakic eyes initially 20/40 or better, the incidence of a reduction in VA to worse than 20/40 attributed to cataract was 20.2% [95%CI: 15.9-25.6]; cataract surgery was performed within 12 months in 13.8 % [95%CI: 11.1-17.2] of the initially phakic eyes. CONCLUSION: Periocular injections were effective in treating active intraocular inflammation and in improving reduced visual acuity attributed to macular edema in a majority of patients. The response pattern was similar across anatomic locations of uveitis. Overall, visual acuity improved in in half of the patients at some point within six months. However, cataract and ocular hypertension occurred in a substantial minority.